Numerical simulation and theoretical study on the impact of wind-sand flow of high-speed trains in long tunnel space - Shiqun Li; Sihui Dong; Yonghua Li; Liping Zhou (Scientific Reports)
Abstract When high-speed trains (HST) run in enclosed spaces such as long tunnels, the thermal accumulation of their suspension devices is continuous and cannot be effectively dissipated. In addition, previous experiments or simulations for the heat dissipation of HST in tunnel spaces did not consider the impact of sand. To clarify the impact of HWS-LT on the heat accumulation of HST equipment cabin, this study used the CFD method to numerically simulate the impact of different wind-sand flow concentrations or no-sand wind on the cooling of equipment in the long tunnel space. Firstly, the sand particles in the wind-sand flow gather at the tunnel entrance and enter the equipment cabin with the train as it enters the tunnel. This boundary condition is more in line with actual engineering situations. Secondly, both flows show asymmetric intrusion into the cabin due to the asymmetrical tunnel arrangement, but the sand particles in the wind-sand flow are affected by the vortices and tunnel walls, resulting in more asymmetric flow and some particles being trapped in the grids or filters, leading to outflow ρ Q  < inflow ρ Q . Under the wind-sand flow condition, the temperature of some equipment surfaces shows more significant increases than under the no-sand wind. Finally, contrary to popular perception, the wind-sand flow carrying sand particles can dissipate heat more effectively than no-sand wind, and the higher the volume fraction φ within a certain concentration range, the better the heat dissipation effect. This is because the wind-sand flow has a higher specific heat capacity, which can remove some heat from the contact point between the sand particles and the equipment wall upon contact. The higher sand particle concentration increases the contact frequency and contact area between the sand particles and the equipment wall, and the heat transfer pathway and heat dissipation efficiency are improved.